Biological evaluation of 2,3-dioxoindolin-N-phenylacetamide derivatives as potent CDC25B and PTP1B phosphatase inhibitors - Qing-Hao Jin; Wen-Bo Chen; Ya-Nan Xia; Bing-Yu Liu; Li-Ping Guan (Universidade de São Paulo, 2020)
A series of 2,3-dioxoindolin-N-phenylacetamide derivatives was evaluated for inhibitory activity against CDC25B and PTP1B enzymes. Most of the derivatives showed inhibitory activity against CDC25B (IC50 = 3.2-23.2 µg/mL) and PTP1B (IC50 = 2.9-21.4 µg/mL). Compound 2h showed the most inhibitory activity in vitro with IC50 values of 3.2 and 2.9 µg/mL against CDC25B and PTP1B, respectively, compared with the reference drugs Na3VO4 (IC50 = 2.7 µg/mL) and oleanolic acid (IC50 = 2.3 µg/mL). The results of selectivity experiments showed that the 2,3-dioxoindolin-N-phenylacetamide derivatives were selective inhibitors against CDC25B and PTP1B. Enzyme kinetic experiments demonstrated that compound 2h was a specific inhibitor with the typical characteristics of a mixed inhibitor. In cytotoxic activity assays compound 2h had potent activity against A549, HeLa, and HCT116 cell lines. In addition, compound 2h showed potent tumor inhibitory activity in a colo205 xenograft model in vivo.